How to report professional practice in nursing? A scoping review. Issue 1 (December 2016) - Poitras, Marie-Eve; Chouinard, Maud-Christine; Fortin, Martin; Gallagher, Frances
Abstract Background Nursing professional practice in different contexts of care has been widely described in evidence-based literature. Currently, there is no consensus on a common structure for these descriptions. Understanding and comparing similar practices is made difficult by the varying nature of descriptions provided in scientific literature. Purpose of the study: 1) to report research methods found in the scientific literature that were used to describe the practice of different health professionals; 2) to report on the main concepts used to describe the practice of these health professionals; 3) to propose a structure for the description of the practice in nursing. Methods A scoping review following a five-stage approach: 1) identifying the research question; 2) identifying relevant studies; 3) selecting studies; 4) charting data; 5) reporting results. The Medline, CINAHL, psychARTICLES, psyCRITIQUES, psycEXTRA, Psychology and Behavioral Science Collection and psycINFO databases were searched. Each study was analyzed and extracted data were classified by categories and structures used to describe the health professional practices. Results Forty-nine studies were included. In these studies, quantitative, qualitative or mixed methods were used to describe professional practice in different health disciplines. Three major concepts were reported most frequently in describing professional practice: roles, domains and activities. The concepts varied greatly among authors. We found that to define roles or to characterize a professional practice, activities must be described and organized on the basis of different domains. Conclusions A promising structure for describing nursing professional practice is proposed by the authors of this review. The structure facilitates the accurate description of all domains and activities performed by nurses in different contexts of practice, and will contribute to the development of knowledge about nursing practice in different contexts based on shared concepts.